CAN ARTIFICIAL INTELLIGENCE REPLACE TEACHERS? (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This scientific article examines whether artificial intelligence can fully replace teachers in the educational process. In recent years, artificial intelligence technologies have developed rapidly and are widely used in education through intelligent tutoring systems, automated assessment tools, and adaptive learning platforms. These technologies have changed the way teaching and learning are organized. The study analyzes both the advantages and limitations of artificial intelligence in education. The results show that artificial intelligence can improve efficiency and personalize learning, but it cannot replace teachers because human emotional interaction, moral guidance, and social development are essential parts of education.
Keywords: Artificial intelligence, teachers, education, learning process, adaptive learning, educational technology, classroom interaction.